Analisis Koreksi Fiskal Terhadap Perhitungan Penyusutan Aset Tetap pada PT Sumatera Prima Fibreboard - Vera Sabiila; Sukmini Hartati; Evada Dewata (Universitas Katolik Soegijapranata, Semarang, 2023)
This activity aims to determine the value of each depreciation according to the commercial and fiscal methods. This methods find out the value of the fiscal correction of depreciation and the PPh that must be paid by PT Sumatra Prima Fibreboard. The type of research used was a qualitative method in the form of data analysis on detailed reports on fixed assets and financial statements in 2020-2022, Tax Regulations based on the Income Tax Law Article 11 No.11 for 2020, Article 11 No.7 for 2021-2022 and Minister of Finance Regulation No.96/PMK.03/2009. Based on data analysis, the results found were that the company's commercial depreciation value from 2020-2022 was different from fiscal provisions. The conclusion in this study was that the company have implemented the right method, namely the straight-line method, but there were several errors in determining the useful life and when the depreciation of fixed assets occurs, which after being corrected had a significant impact on income tax and net profit generated at PT Sumatra Prima Fibeboard